Effects of Sound Stimuli Applied in Branding: An Empirical Study of Its Antecedents and Consequences - Wu, Wann-Yih; Fu, Chen-Su; Huang, Hua-Sheng; Wang, Hong-Chun (Asian Journal of Business and Accounting, 2010)
Intel and Nokia’s success in sound branding encouraged followers to implement this branding strategy. This study aims to explore the effects of sound stimuli applied in branding. A questionnaire survey was conducted to measure consumers’ perception towards sound stimuli, and its influence towards brand preference. Consumers’ perception towards sound stimuli is further examined to identify its influences on attitude towards the brand, brand awareness with brand association, and qualitative perception. Brand loyalty and preference are confirmed to have consequential influences from the antecedents: attitude towards the brand, brand awareness with brand association, and qualitative perception. Findings of this study suggest that sound trademarks should be carefully selected and designed to help consumers remember the brand and elicit positive awareness, association, attitude and perception. In contrast, slogan-alone sound trademarks, especially those with ambiguous meaning slogans, may lead to negative attitudes and preferences.